Sense of coherence and health condition in parents of children with cancer - Dymecka, Joanna (Psychoonkologia, 2013)
The sense of coherence is one of the most important variables which protect health from the destructive influence of life situations. The aim of this study was to analyse the relationship between the child oncological disease, parents health condition and sense of coherence. The study used survey and Sense of Coherence Scale SOC-29. The study included 25 parents of children with cancer staying in the hospital with their children. Child oncological disease affect the poor physical health of parents, this is particularly true in parents with low levels of SOC. Sense of coherence in the interaction of stress associated with child disease on parents’ health of the child oncology serves as moderator protecting health in stressful situations.